Low-elevation endemic Rhododendrons in China are highly vulnerable to climate and land use change - Fangyuan Yu (Elsevier, 2021)
The combination of climate change and land use change may have profound effects on terrestrial biodiversity in more significant ways than either has separately. However, most studies focus largely on the climate change impacts, which hampers our ability to develop appropriate conservation strategies in a dramatically changing world. Here, we predict the distributions of 191 Chinese endemic Rhododendron species under future climate and land use change, combining two dispersal constraint scenarios by using a species distribution model. We then assess the vulnerability and extinction risk of these species and identify areas at risk of highest species loss. We find that 52% of the species are predicted to expand and shift their geographic ranges, typically to the northwest and north. The remaining 48% of species are predicted to contract in geographic ranges under the 'perfect-dispersal' scenario. And only 7% of Rhododendron are predicted to keep 'still', while the rest of species shrank with varying degree under the 'no-dispersal' scenario. Species lost particularly at lower elevations, and we also identify four regions at particularly high risk from the impacts of climate and land use change, namely the parallel ridge-and-valley areas of eastern Sichuan, southeastern Tibet, western and eastern Yunnan, southern Shaanxi, plus scattered areas in Guangdong, Hainan and Taiwan. We conclude that Chinese endemic Rhododendron species at lower elevations are highly vulnerable to climate and land use change, facing an elevated risk of extinction under varying scenarios. These species therefore call for more attention and protection. We highlight the critical role of endemic Rhododendron species as good indicators for measuring, evaluating and understanding the effectiveness of our biodiversity conservation efforts. Our work provides insight into the status, trends and threats regarding endemic Rhododendron species, identifying risks and prioritizing conservation in a rapidly changing world.